Pediatric hospitalizations attributable to rotavirus gastroenteritis among Cambodian children: Seven years of active surveillance, 2010–2016. Issue 51 (14th December 2018) - Angkeabos, Nhep; Rin, En; Vichit, Ork; Chea, Choeung; Tech, Ngorn; Payne, Daniel C.; Fox, Kimberley; Heffelfinger, James D.; Grabovac, Varja; Nyambat, Batmunkh; Diorditsa, Sergey; Samnang, Chham; et al.
Abstract: Background: Each year, approximately 1, 066 Cambodian children under five years old die of diarrhea, and 51% of these deaths are due to rotavirus gastroenteritis. Quantifying childhood hospitalizations caused by severe rotavirus infections is also important in demonstrating disease burden caused by this virus. The objective of this study is to update and confirm the current burden of pediatric hospitalizations attributable to rotavirus gastroenteritis among Cambodian children using seven years of continuous active, prospective surveillance from 2010 to 2016. We also characterize the circulating rotavirus genotypic strains during this period. Methods: Active surveillance for rotavirus gastroenteritis was conducted from January 2010 through December 2016 at a national hospital in Phnom Penh, Cambodia. Children <60 months of age who were hospitalized for acute gastroenteritis (AGE) were consented and enrolled. Information on gender, age, clinical characteristics, and month of onset were collected. Stool specimens were collected and tested by enzyme immunoassay for the presence of rotavirus antigen, and genotyping was performed on rotavirus test-positive specimens to characterize predominant rotavirus strains during the surveillance period. Results: Of 7007 children enrolled with AGE and having specimens collected, 3473 (50%) were attributed to rotavirus gastroenteritis. The majority of rotavirus hospitalizations occurred in children younger than two years old (92%). Year-round rotavirus transmission was observed, with seasonal peaks during the cooler, dry months between November and May. Genotypic trends in rotavirus were observed over the surveillance period; the predominant rotavirus strains changed from G1P[8] (2010–2012), to G2P[4] (2013–2014), the emergence of genotype G8P[8] in 2015, and G3P[8] in 2016. Conclusions: Rotavirus is the leading cause of severe acute gastroenteritis hospitalizations in Cambodian children under five years old, with 50% of such hospitalizations attributable to rotavirus. Over 90% of rotavirus hospitalizations occurred in children under 2 years of age. Changes in the predominant rotavirus strains occurred over time among these unvaccinated children. This information is important to understand and prioritize the current potential impacts upon child health that could be achieved through the introduction of rotavirus vaccines in Cambodia.